Climatic imprint of the mid-latitude Westerlies in the Central Tian Shan of Kyrgyzstan and teleconnections to North Atlantic climate variability during the last 6000 years. (August 2014) - Lauterbach, Stefan; Witt, Roman; Plessen, Birgit; Dulski, Peter; Prasad, Sushma; Mingram, Jens; Gleixner, Gerd; Hettler-Riedel, Sabine; Stebich, Martina; Schnetger, Bernhard; Schwalb, Antje; Schwarz, Anja
In general, a moderate drying trend is observed in mid-latitude arid Central Asia since the Mid-Holocene, attributed to the progressively weakening influence of the mid-latitude Westerlies on regional climate. However, as the spatio-temporal pattern of this development and the underlying climatic mechanisms are yet not fully understood, new high-resolution paleoclimate records from this region are needed. Within this study, a sediment core from Lake Son Kol (Central Kyrgyzstan) was investigated using sedimentological, (bio)geochemical, isotopic, and palynological analyses, aiming at reconstructing regional climate development during the last 6000 years. Biogeochemical data, mainly reflecting summer moisture conditions, indicate predominantly wet conditions until 4950 cal. yr BP, succeeded by a pronounced dry interval between 4950 and 3900 cal. yr BP. In the following, a return to wet conditions and a subsequent moderate drying trend until present times are observed. This is consistent with other regional paleoclimate records and likely reflects the gradual Late Holocene diminishment of the amount of summer moisture provided by the mid-latitude Westerlies. However, climate impact of the Westerlies was apparently not only restricted to the summer season but also significant during winter as indicated by recurrent episodes of enhanced allochthonous input through snowmelt, occurring before 6000 cal. yr BP and at 5100–4350, 3450–2850, and 1900–1500 cal. yr BP. The distinct 1500-year periodicity of these episodes of increased winter precipitation in Central Kyrgyzstan resembles similar cyclicities observed in paleoclimate records around the North Atlantic, likely indicating a hemispheric-scale climatic teleconnection and an impact of North Atlantic Oscillation (NAO) variability in Central Asia.